L’analyse de données à partir de livres des voyageurs : deux études de cas dans les Alpes - Jérémie Magnin; Patrick Vincent (Mondes du Tourisme, 2023)
The Swiss Guestbook Project aims to preserve and study visitors’ books produced in Switzerland and neighboring Savoy before 1914. Situated at the interface between a qualitative and quantitative approach, the visitors’ book presents a series of methodological problems, particularly concerning the reliability of the data but also the importance that should be given to the texts. In this article, we briefly present the project and the current state of research before discussing two case studies. The first concerns the Monte-Rosa and Riffelhaus hotels in Zermatt between 1854 and 1866. In the second, we compare the cross-data of three books from the Chamonix valley in 1854. Our calculations of the number and origin of travelers demonstrate the contributions and limitations of these documents as statistical sources, while the analysis of the texts allows us to better understand their relevance to the development of mountaineering knowledge.